PENERAPAN DATA MINING UNTUK PEMESANAN PEMESANAN PERCETAKAN BAHAN AJAR DENGAN ALGORITMA APRIORI (STUDI KASUS : PERCETAKAN WENDY) - Nurmawaty Hutabarat; Jijon Raphita Sagala (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2018)
Wendy's printing is one of the printing presses in collaboration with the University of Santo Thomas, especially in the field of computer science, the printing of Wendy is located on the faithful road of UNIKA campus intersection. Print leaders and employees sometimes have difficulty finding out how much teaching material has been printed in one transaction, so that the leader of Wendy's printing press is still manual / speculating in teaching material.The application of data mining for ordering the teaching of teaching materials at the computer science faculty of the university of Saint Thomas is designed to produce this rule can produce rules / rules of association can be seen and analyzed the results, so that the printing leader can see a frequency of teaching materials that often occur in each transaction.Therefore, analysis and testing is carried out, it is hoped that it can provide information about the transaction patterns of teaching materials that often appear. So that it can help the owner in making decisions to order and print teaching materials.